Quantificação da glutationa reduzida em eritrócitos humanos por cromatografia líquida de alta eficiência-uv: validação e aplicação - Schott, Karen Lilian (2005)
Oxidative stress may be initiated by a decline in the antioxidant defence system or by an overproduction of free radicals leading to an imbalance between oxidants and antioxidants. The most significant alteration in the antioxidant defence is a decrease in reduced glutathione (GSH) concentration. GSH depletion is linked to a number of disease states; including cancer, neurodegenerative and cardiovascular diseases. GSH is the main nonprotein thiol involved in the antioxidant cellular defence against xenobiotics and naturally occurring deleterious compounds, such as free radicals and hydroperoxides. GSH not only protects cell membranes from oxidative damage, but also helps to maintain the sulphydryl groups of many proteins in the reduced form, a requeriment for their normal function. Free radicals induce lipid peroxidation that plays important roles in the pathological process of many diseases such cardiovascular diseases. Given the role of GSH in the protection against oxidative stress and detoxification of xenobiotics, its availability in the reduced form may be a key factor in the maintenance of health. Therefore, its determination in human erythrocytes is necessary. Metodologies for measuring GSH in human biological samples and their feasibility as routine methods in the clinical chemistry laboratory are important. The high-performance liquid chromatography (HPLC) became recently the method of choice for measuring GSH, because it is rapid, highly specific, sensitive and reproducible. Recent reports describe the use of HPLC with fluorescence detection of derivatives or electrochemical detection of the sulphydryl groups, however these detectores are not as widely available as ultraviolet-visible models. For the HPLC analysis of blood samples, the removal of proteins is the most important cleanup step. In this study, a method was optimized and validated to determine the human erythrocyte GSH by HPLC, gradient elution, with ultraviolet detection, wavelength 330 nm. The separation was performed on a C18 column integrated with guard-column, at 39°C. Pre-column derivatization was performed with 5, 5´-dithio-bis (2-nitrobenzoic) acid (DTNB), Ellman´s reagent. The erythrocytes were separed, hemolized and deproteinized with 15% trichloroacetic acid before the derivatization. The analytical parameters were evaluated: linearity, selectivity, precision, accuracy, limit of detection, limit of quantification, robustness, recovery and stability. The optimized method was applied in healthy human (control group) and patients receiving hemodialysis treatment. The assay was linear from 0.5 to 3.0 mM. The relative standard deviation for intra- and inter-day precision was lower than 10% with accuracy (%bias) was within ± 10% for the three GSH concentrations. The average recovery of GSH from erythrocytes was over 94%. The limit of detection was 0.0024 mM and the limit of quantification was 0.0081 mM. Derivatized samples with DTNB showed good stability for a month at 20°C. The method was evaluated in blood samples from healthy subjects and hemodialyzed patients. Erythrocyte GSH levels of patients were significantly (p<0.05) increased when compared with control group. Many patients received vitamin supplementation, 70% and erythropoietin, 75%. The healthy subjects showed GSH levels similar to previous reports. The results demonstrated that the optimized method is linear, reproducible, provided low limit of detection and quantification, and is feasible.